(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
The word Plagiarism has a Latin origin, “plagiarius,” meaning “kidnapper” or “abductor” and “plaga” meaning “hunting net” 1,2 The term is very old and has many definitions. The Committee on Publication Ethics (COPE) define plagiarism as “the unreferenced use of others published and unpublished ideas.”3 The authors, however must be cautious that using published photos, videos, images, art work, graphs and tables without written permission is also plagiarism.2 Plagiarism is the most common among ethics issues in research and although there are many forms of plagiarism like collusion plagiarism, self-plagiarism, technical plagiarism, patchwork plagiarism, and blatant plagiarism none is acceptable ethically and legally.4 The exact prevalence of plagiarism is not known.1 However some studies have reported a rejection rate of 9.8% to 16% research papers due to plagiarism and a higher incidence of plagiarism has been reported in some countries like Japan, Korea, Italy, France, China, Iran, Turkey and India.5,6